Experimental developments of A2RAM memory cells on SOI and bulk substrates. (January 2015) - Rodriguez, Noel; Gamiz, Francisco; Navarro, Carlos; Marquez, Carlos; Andrieu, François; Faynot, Olivier; Cristoloveanu, Sorin
Highlights: A2RAM devices have been fabricated on 2.5 μm and 22 nm technologies. The fabrication is compatible with the CMOS process. The electrical characteristics show good performance in all aspects studied. Abstract: A2RAM prototype devices have been demonstrated in both SOI and bulk technologies. The fabrication process has successfully achieved the characteristic retrograde doping profile of the channel which allows the coexistence of electrons and holes in the same body while maintaining low-voltage single-gate operation. The different prototypes have been electrically characterized, all of them exhibiting memory effect. The SOI samples present the best performance, showing very attractive current margin between states, competitive retention time, reasonable variability, immunity to disturbance events and no endurance issues even in the short-channel devices fabricated in the most advanced 22 nm process.